Study of wall thickness and its impact on microstructure on 316L manufactured with Direct Metal Laser Sintering - Nalum, Daniel; Timhagen, Johanna (My University, 2017)
The aim off this thesis was to theoretically and experimentally study how the microstructure of additively manufactured 316L (stainless steel) components is affected by different wall thicknesses. In addition, hardness and porosity are analyzed with a perspective of wall thickness. In this study 9 different thicknesses, ranging from 0,2 mm up to 3 mm, were selected. The structure was cut in a way so that the middle part of each wall could be observed to exclude edge defects. The samples were analyzed with a Leica DMi8 microscope was pictures was taken and stitched for a porosity analyses. The analysis showed a low number of pores which were overall small. A Vickers hardness measurement was done in a Struers DuraScan to observe if the wall thickness affected the micro hardness of the material. No significant correlation was found and the hardness does not seem to be affected by either wall thickness, position of cross section or edge effects. Electrochemical etching was performed to reveal the microstructure of the material. Melt pools, solidification structure and sub-grains emerged during this process. A more detailed investigation was conducted and the solidification structure of the material was observed. The result shows a microstructure containing large areas of sub-grains with the same orientation, creating a columnar solidification structure which follows the building direction. The results indicate that the orientation of the grains is affected by the wall thickness.
Keywords: Materialvetenskap; Maskinteknik; Materialteknik; Materials Science; Mechanical Engineering; Materials Engineering